Formación para el aprendizaje continuo y para el trabajo en grupo: guías interactivas multimedia - Ciancio, Gustavo (2005)
As physics teachers we faced the challenge to introduce our freshmen engineering students not only into the world of Physics but also into the skills and abilities necessary to learn, analyze and criticize different situations. Besides, to fulfill present professional requirements they need to learn to work within a team and report that work results. In this paper we show one of the instructional strategies we have developed to help freshmen university students to get those capacities and methods, which are basic for their future qualification. The didactic approach, which is also aimed to promote in the students commitment to topics not addressed in depth in the classroom, uses the tools provided by the new technologies and the findings of modern research on students learning. The multimedia guides produced are based in predictions and observation of real time and taped experiments. These are employed to introduce and lead groups of four students to learn (or to go deeper into), within the Newtonian frame, special topics like precession motion and real fluids static. As outcome of the proposed activities, the group should produce a written report and find practical application of the physical concepts addressed.